Determining potential natural and anthropogenic drivers of adrenocortical activity in African clawless otters (Aonyx capensis) by evaluating faecal glucocorticoid metabolite concentrations - Ganswindt, Andre (University of Pretoria, 2023)
Dissertation (MSc (Zoology))--University of Pretoria, 2023.